Pengaruh Digitalisasi Perbankan terhadap Kepuasan Nasabah Bank BCA - Ani Pebrianti; Nanda Pricilia Dara Dinanti (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
The rapid advancement of digital technology has driven a significant transformation in the banking sector, including Bank Central Asia (BCA), one of Indonesia’s largest private banks. BCA has pioneered the implementation of digital services such as mobile banking, internet banking, and AI-based customer service. This study aims to analyze the impact of banking digitalization on customer satisfaction at BCA and to identify the most influential digitalization factors. A quantitative approach was used, employing a survey method through questionnaires distributed to active users of BCA's digital services. The collected data were analyzed using multiple linear regression to examine the relationship between digitalization variables—such as convenience, service quality, transaction security, employee engagement, and digital innovation—and customer satisfaction. The findings are expected to provide empirical evidence on how digitalization influences customer satisfaction and loyalty, and to serve as the basis for strategic recommendations for BCA to enhance its digital services. Additionally, this research contributes to the theoretical development of digital banking management in the Indonesian context.